Constructing an index of corporate social responsibility practices in Oman / Afshan Younas, Aza Azlina Md Kassim and Abul Bashar Bhuiyan - Younas, Afshan; Md Kassim, Aza Azlina; Bhuiyan, Abul Bashar (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
The importance of Corporate Social Responsibility (CSR) has been acknowledged greatly as an objective of business sustainability. Whereas the measurement of CSR is always a source of argument among researchers. There are different approaches identified and used by researchers to measure CSR. The main objective of this study is to measure CSR disclosure by constructing an index based on content analysis. The study used non-financial listed companies’ data in Oman to construct an index for the period of 2016 to 2019. A total of 291 firm-year observations are used in this study to construct and measure the CSR disclosure index. We employ 40 elements to measure CSR disclosure based on five sub-themes. The result of the study reveals that as CSR disclosure requirement is mandatory in Oman according to the new corporate governance system, the listed companies are contemplating to cope and develop CSR charters. The evidence indicates that some companies have high CSR disclosure while others are still struggling to develop CSR charter and disclose their activities. However, CSR disclosure improves significantly from 2016 to 2019, which shows a strict implementation of the code of corporate governance.